FEATURES OF BONE WOUND REGENERATION USING OSTEOPLASTIC MATERIALS - S.P. Yarova; Yu.I. Sylenko (Український стоматологічний альманах, 2025)
The aim of the study was to microscopically evaluate the features of bone regeneration in an infected experimental wound using osteoplastic materials and their combined use with a two-layer membrane “Hyprosorb F”.